SELECTION IN TEAM SPORTS - ANALYSIS OF SPECIALIST OPINIONS - Dragoș Ioan TOHĂNEAN (Editura Universitatii Transilvania din Brasov, 2019)
This paper represents a study on the opinions of the specialist practitioners (coaches) regarding the selection process in team sports. A questionnaire was used and that was applied for 109 coaches in Romania. General aspects related to the selection as well as the relevance of some psychological criteria of sports selection were addressed. The general conclusion of this research was that a significant part of the respondents considered that the selection process in team sports is inappropriate, which requires a careful analysis of the possible causes.